Determination of output factors for the Leksell gamma knife using ion chamber, thermoluminescence detectors and films - (:unkn) unknown (My University, 2006)
Purpose: In stereotactic radiosurgery by the Leksell gamma knife, small fields of 4-18 mm in diameter are used. The difficulties associated with the dosimetry of small radiosurgical beams are well known. The output factors for small field sizes show a strong field size dependence, with rapidly decreasing output factors as the diameter of the field decreases. The main purpose of this study was to determine output factors of 18, 14, 8 and 4 mm collimators for Leksell gamma knife and to compare them with the values given by the manufacturer. Materials and methods: The relative output factors of the 18, 14, 8 and 4 mm collimators for model B Leksell gamma knife were measured. The output factor measurements were performed using a PTW 0.125 cc ion chamber, G200 thermoluminescence detectors (TLDs), Kodak XV and Kodak ERD2 films. Results: For 14 mm collimator, output measurements used with anion chamber, TLD, Kodak XV film and Kodak ERD2 film were in agreement with the manufacturer's estimates within 1%. For 8 and 4 mm collimators, the best agreement with values given by the manufacturer were obtained by Kodak EDR2 films (2% and 5%, respectively). Conclusion: The measured output factors are in good agreement with the values recommended by the manufacturer for 18, 14 and 8 mm collimators. No good agreement was found for 4 mm collimator. © 2006 Zerbinis Medical Publications.
Keywords: Gamma knife; Kodak XV-ERD2 film; Output factors; Stereotactic radiosurgery; Thermoluminescence detector